Gingival Stem Cell‐Conditioned Media and Low‐Level Laser Therapy Enhance Periodontal Ligament Stem Cells Function by Upregulating Wnt and TGF‐β Pathway Components: An In Vitro Study - Mohammed Y. Aljabri; Yaser A. Alhazmi; Salah A. Elsayyad; Shehabeldin M. Saber; Mohamed Shamel (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study investigated the synergistic effects of gingival stem cell conditioned media (GSC‐CM) and low‐level laser therapy (LLLT) on stimulating PDLSCs, explicitly focusing on the molecular basis of enhancing the Wnt and TGF‐β signaling pathways. Material and Methods PDLSCs were isolated and GSC‐CM were prepared and characterized. Five groups were utilized: control, osteogenic induction medium (positive control), GSC‐CM, LLLT (980 nm, 1.5 J/cm²), and a combination of GSC‐CM with LLLT. Cell viability was assessed using the MTT assay on Days 1, 2, and 3. Osteogenic differentiation of PDLSCs was assessed using mineralization assays employing Alizarin Red staining, and molecular analyses of osteogenic markers (RUNX2, ALP, OCN) and signaling‐related genes (CTNNβ1, TGFβ1) conducted via RT‒PCR. Results The findings revealed that the dual application of GSC‐CM and LLLT significantly enhanced cell viability and osteogenic differentiation of PDLSCc compared to the effects of the individual treatment modalities. Moreover, the study revealed elevated expression levels of osteogenic markers across all the experimental groups, specially the combination group, which showed the highest levels. Significantly, the combination treatment group displayed superior outcomes in this regard. The results also suggest potential activation of Wnt/β‐catenin and TGF‐β signaling components. Conclusions This study highlights the significant effects of using GSC‐CM and LLLT to improve PDLSC survival and osteogenic differentiation.